Fiqh Hisab Arah Kiblat: Kajian Pemikiran Dr. Ing Khafid dalam Software Mawāqit - Anisah Budiwati (Universitas Islam Indonesia, 2014)
This study analyzes the software determining the direction of Qibla by Dr. Ing. Khafid,geodesy experts in BIG (Goespasial Information Agency) in Mawāqit version 2001.06. Theanalysis was conducted using qualitative methods. These results indicate that the system ofreckoning Qibla direction of Dr. Ing. Khafid is in Mawāqit program version 2001.06. usingcalculations spherical trigonometry. In addition, see the pattern fiqh qibla direction, he soughtto translate the arguments Shar'ie existing in the language of science in line with the opinion ofImam Syafi‟i, although there are differences.